The use of hop for making bread with health improving properties - Protsenko, Lidia; Pasitschnyk, Irina; Yurchak, Vera (My University, 2013)
The authors researched biochemical indices of delicate aromatic and aromatic hop sorts Klon 18, Zlato Polissya, Slovyanka, Zagrava, Gaidamatsky and found that Zlato Polissya and Gaidamatsky are the most promising for bakery as they contain more polyphenols. Natural hop preparation with reduced content of bitter compounds, containing 2,5-3 times less α-acids and having slightly reduced by 8-9% content of polyphenols has been elaborated. It gives possibility to increase hop dose and enrich bread with polyphenols and other valuable hop compounds not increasing the excessive bitterness.
Keywords: hop; hop preparation; biologically active compounds; bread; quality; хміль; хмелевий препарат; біологічно активні компоненти; хліб; якість; хмель; хмелевой препарат; биологически активные компоненты; хлеб; качество; кафедра технології хлібопекарських і кондитерських виробів